Menari dengan Kata-Kata: Kritik Mahbub Djunaidi terhadap Kebijakan Pemerintah Indonesia 1970 – 1990 - Wahyudhi, Johan (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
This paper describes Mahbub Djunaidi, a social activist, journalist and writer who often protested against government policies from 1970 to 1990. During this period, Indonesian Muslims lived in a different social and political atmosphere than before. Previously, Muslims in Indonesia were relatively free to express their thoughts and political activities, but during this 20-year period, the situation became more restrictive. President Soeharto's government allegedly carried out a series of restrictive actions to inhibit political freedom and intellectual development for some Muslims, especially those belonging to Nahdhlatul Ulama, the largest Islamic mass organisation in Indonesia at that time. This paper will use an intellectual history approach by putting forward a number of Mahbub's writings relating to his criticism of the Soeharto government. Mahbub's writing style is known for combining humour and satire, making him one of the most prominent columnists in Indonesia at the time.